Comparison of dual antiplatelet therapy prescribed as one-pill versus two-pill regimen - Lim, Woo-Hyun; Chae, In-Ho; Yoon, Chang-Hwan; Choi, Dong-Ju; Lim, Sang Wook; Park, Woo Jung; Doh, Joon-Hyung; Kim, Sang-Hyun; Kim, Myung-A.; Lee, Seung-Hwan; Yoon, Jung Han; Ahn, Young Keun; Hyon, Min-Su; Kim, Ki Seok; Kim, Young Kwon; Lee, Han Cheol; Seol, Sang-Hoon; Hwang, Kyung-Kuk; Choi, Si-Wan; Han, Kyoo-Rok; Shin, Eun-Seok; Kim, Sang-Wook; Lee, Byoung Kwon; Kim, Hyo-Soo (Thrombosis and Haemostasis, 2016)
Fixed-dose combination (FDC) drugs can simplify the medication regimen and potentially improve adherence. However, evidence is lacking about the efficacy and safety of FDC drugs of clopidogrel plus aspirin. Individual data from the three independent MR-CAPCIS trials were pooled and analysed. In those trials, subjects who had been treated with either dual antiplatelet therapy (DAPT) or aspirin alone after drug-eluting stent (DES) implantation were randomly assigned to one-pill or to two-pill DAPT group. Platelet reactivity was measured with VerifyNow-P2Y12 and aspirin point-of-care assays at baseline and eight weeks after treatment. In the present study, primary efficacy endpoint was changes in platelet reactivity unit (PRU) between baseline and eight weeks. A total of 965 subjects were analysed. In prior clopidogrel and aspirin users, PRU was well maintained regardless of switching to either one-pill or two-pill DAPT (ΔPRU=0.4 vs 0.0, p=0.939). In prior aspirin users, PRU was decreased by 73.7 in one-pill DAPT and 77.5 in two-pill DAPT group, with no differences between them (p=0.499). The incidence of high on-treatment platelet reactivity at eight weeks, defined as PRU≥235 in Western people, was 34.8 % in one-pill DAPT group and 37.6 % in two-pill DAPT group (p=0.380), and that defined as PRU ≥275 in Oriental people was 17.7 vs 21.7 % (p=0.129). Independent predictors of high platelet reactivity on clopidogrel were female gender, increasing age, and diabetes. Study drugs were well tolerated. In conclusion, FDC one-pill DAPT showed similar efficacy to two-pill DAPT in terms of platelet reactivity in patients receiving DES in Korea.
Keywords: Aspirin; clopidogrel; dual antiplatelet therapy; fixed-dose combination